Bali Hari Ini: Permasalahan Kepariwisataan dan Solusinya - AA Gede Yuniartha Putra (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Bali tourism that already has such a large name in the global context. As a result of the development of tourist visits, various tourism facilities were established such as restaurants, artshop, art market, entertainment centers, and recreation places in the tourist destination and around tourist attractions. Tourism in Bali is very meaningfull to the tourism industry and local communities. However, this international tourist destination has problems here and there. This study finds that the problems faced are tourism destinations, tourism institutions, tourism marketing, and tourism industry. The problems have been handled significantly. Nevertheless, in the future, it is hoped that tourism will be increasingly enhanced in all its respects so that this business will also increasingly provide welfare for all involved.